Research Advances in How the cGAS-STING Pathway Controls the Cellular Inflammatory Response - Wan, Dongshan; Jiang, Wei; Hao, Junwei (Frontiers in Immunology, 2020)
Double-stranded DNA (dsDNA) sensor cyclic-GMP-AMP synthase (cGAS) along with the downstream stimulator of interferon genes (STING) acting as essential immune-surveillance mediators have become hot topics of research. The intrinsic function of cGAS-STING facilitates type-I interferon (IFN) and other inflammatory signaling responses. The cGAS-STING pathway modulates cellular processes such as autophagy, cell survival, senescence and interplays with other innate immune pathways, by which it participates in regulating infection, inflammatory disease and cancer. The therapeutic approaches targeting this pathway show promise for future translation into clinical applications. Here, we present a review of the important previous works and recent advances regarding the cGAS-STING pathway, and provide a comprehensive understanding of the modulatory pattern of the cGAS-STING pathway under diverse pathologic states.